Evaluating the Redesign of an ICU Bedside Emergency Equipment Drawer. (September 2013) - Harris, Bonnie; Ford, Nicholas; Grundgeiger, Tobias; Venkatesh, Bala; Sanderson, Penelope
Patient safety can be improved by redesigning how medication and bedside equipment is stored in the intensive care unit (ICU). Grundgeiger (2011) noted that an ICU emergency bedside drawer often was not fully stocked. He used human factors principles to design an illustrated and divided drawer that significantly improved drawer restocking compliance and is still in use in the ICU. In two studies we set out to clarify exactly why Grundgeiger's redesign succeeded. In Experiment 1 we tested the redesigned vs. old drawer design using stationery contents and psychology student participants. In Experiment 2 we used the tests developed in Experiment 1 to compare ICU nurses' performance with the redesigned vs. old drawer design. Both experiments indicate that the divided and illustrated drawer leads to faster restocking times and overwhelmingly positive user acceptance.